EFFECTS OF L-ASCORBIC ACID AND ALPHA-TOCOPHEROL ON BIOCHEMICAL PARAMETERS OF SWIMMING-INDUCED OXIDATIVE STRESS IN SERUM OF GUINEA PIGS - BursaÄ‡-MitroviÄ‡, Marija; MilovanoviÄ‡, Dragan R.; MitiÄ‡, Radoslav; JovanoviÄ‡, Danijela; SovrliÄ‡, Miroslav M.; VasiljeviÄ‡, Perica; TomoviÄ‡, Jovica; ManojloviÄ‡, Nedeljko (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The purpose of this study is to determine the effect of L-ascorbic acid and alpha-tocopherol as well as combination ofthese vitamins with or without exposure to physical exercise on intensity of lipid peroxidation, activity of xanthine oxidase, activityof total antioxidative system, concentration of glutathione, and activity of catalase in the serum of guinea pigs.Materials and Methods: The experimental measurements of intensity of lipid peroxidation, activity of xanthine oxidase, activity oftotal antioxidative system, concentration of glutathione, and activity of catalase were done in the serum of guinea pigs. The animalswere exposed to the test load to achieve exhaustion and the test was terminated when the animal for the third time to sink into thewater.Results: The results of this study demonstrated that endurance exercise of guinea pigs induced oxidative stress response in terms ofincreased lipid peroxidation and activity of xanthine oxidase in the serum of experimental animals. Our study investigated theantioxidant activity of L-ascorbic acid and alpha-tocopherol also measuring three protective markers in the serum: total antioxidantactivity, content of glutathione and activity of catalase. The results obtained show that the vitamins influence the concentrations ofabove mentioned biochemical parameters, which points out their protective effect of swimming-induced oxidative stress.Conclusion: Single or combined administration of L-ascorbic acid and alpha-tocopherol caused significant inhibition of thesemarkers indicating the important antioxidant activity of the vitamins. Results lead to conclude that the combined treatments withvitamins with or without exposure to physical exercise showed the clear synergistic effect.